Photosensitive ZnO‐Graphene Quantum Dot Hybrid Nanocomposite for Optoelectronic Applications. Issue 7 (25th May 2016) - Aaryashree,; Biswas, Sagar; Sharma, Pankaj; Awasthi, Vishnu; Sengar, Brajendra S.; Das, Apurba K.; Mukherjee, Shaibal
Abstract: Inorganic‐organic hybrid nanostructures consisting of graphene as the organic part are being explored for various applications. Graphene quantum dots (GQDs) have gained popularity among other semiconductor quantum dots due to their distinct and interesting properties. Here, we have studied various properties of the electrodeposited hybrid nanocomposite consisting of ZnO and graphene‐QDs (ZnO_GQD) along with the electrodeposited ZnO and GQDs individual films. It is observed that although GQDs do not change the properties of ZnO, but its addition shifts the PL peak of ZnO and also introduces some interesting changes in other electrical and optical characteristics. The values of photosensitivity of ZnO, GQD, and ZnO_GQD nanocomposite were found to be 6.77, 51, and 99.32, respectively at room temperature. The enhancement of photosensitivity of ZnO_GQD nanocomposite was 1.9‐fold and 14.67‐fold as compared to that of GQDs and ZnO, respectively. Owing to the convenience and cost‐effectiveness of the current deposition technique, these nanohybrids can be grown onto different substrates to improve the characteristics of the ZnO_GQD nanocomposites. The enhanced photosensitivity of the nanohybrids can hold immense potential for the application in UV‐Vis optoelectronic devices. Abstract : The absence of bandgap in graphene has restricted the graphene based hybrids in applications such as fuel cells, batteries, photovoltaics and sensors. Here, we have used a simple electrochemical method to prepare hybrid material consisting of ZnO and graphene quantum dots as inorganic and organic precursors respectively and done a comparative study with its predecessors. Results showed that addition of quantum dots not only increased the band gap of ZnO to 3.33 eV but also improved upon its I–V characteristics.